Coaxial pulsed 3 MW RF power input for 176 MHz accelerating structure - Auslender, V.L.; Chernov, K.N.; Gornakov, I.V.; Kazarezov, I.V.; Makarov, I.G.; Matyash, N.V.; Ostreiko, G.N.; Panfilov, A.D.; Serdobintsev, G.V.; Tarnetsky, V.V.; Tiunov, M.A.; Shachkov, V.E. (Вопросы атомной науки и техники, 2008)
Design of the power input is described in the paper. The power input is a low-impedance coaxial line with the wave resistance of about 30 Ohm. One of the line ends is shorted, the other turns into the coupling loop, which inductance is compensated by the stray capacitance. The vacuum section of the power input is separated from the atmosphere by the cylindrical insulator made of 22XC ceramics. The coaxial part of the power input is divided into the 176 MHz quarter-wave-length insulator and quarter-wave-length transformer by the point of the 50 Ohm RF power feeder connection. Power input testing technique is described in the paper together with the results obtained when operating at the high power level.